PENERAPAN MODEL PROBLEM BASED LEARNING MATERI GEOMETRI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IV SD NEGERI 03 LANGENHARJO - Aslam, Avriza; Rofian; Sukamto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the results of observations and interviews which state that 1) Students are accustomed to learning only by using the method of listening to teacher explanations and practicing questions which makes the lack of students actively involved in learning. 2) Students without supervision and motivation from parents is also a factor in students' lack of awareness in learning. 3) Students have difficulty understanding the material because they do not pay attention to the teacher's explanation. This can be seen from student score data. The purpose of this research is: to determine students' problem solving abilities by applying the model Problem Based Learning (PBL) Geometry material for class IV SD Negeri 03 Langenharjo. The research used is quantitative research, with the type of research used being research experimental design. Study experiment namely research used to find the effect of certain treatments on others under controlled conditions, whereas design Research is a design on how to analyze data so that it can be carried out in accordance with research objectives. The design used is one grup pre-test And post-test design. The research results show that the application of the model problem based learning effective in improving students' problem solving abilities in geometry material in class IV. This is shown in the results of the Paired Sample T Test calculation. The final data obtained is the result that is the value sig.(2-tailed) 0.0000 which means it is smaller than 0.05. Thus it can be concluded that Ho is rejected and Ha is accepted.